Exploring mass media exposure and perception of terrorism threats among residents in Ibadan, south west Nigeria (2023)
There is a growing consensus globally that a symbiotic relationship exists between the media and terrorism. In the light of ongoing security situation confronting Nigeria, it has become very critical to analyze and understand people’s perception of terrorism threats. Previous studies have focused greatly on media coverage of terrorism while there appears to be dearth of studies exploring the correlation between citizens’ perception of terrorism threat and their exposure to the mass media. This study, therefore, investigated exposure to mass media and perception of terrorism threats among the residents in Ibadan South West Nigeria. The study adopted cultivation theory while cross-sectional survey served as the research design. Probability and non-probability (stratification, simple random, purposive and convenient) procedures were employed in selecting (n=339) respondents. Results revealed that perceived level of terrorism threats to self and the community to be high while no significant relationship exists between exposure to mass media information on terrorism threats and perceived terrorism threats to self and community among residents in Ibadan. The study recommends that the federal and state authorities overhaul their security apparatuses and strategies in addressing the challenges of terrorism threats in the country.